2004
DOI: 10.1007/s00221-003-1797-6
|View full text |Cite
|
Sign up to set email alerts
|

Coordinating degrees of freedom during interceptive actions in children

Abstract: The aim of the experiment was to examine how children coordinate the degrees of freedom of the arm and trunk when performing interceptive actions that correspond to daily life activities. For that purpose, children were required to reach and grasp a stationary ball while standing (condition C1), a stationary ball while walking (C2), and a moving ball while standing (C3). The resulting movements were measured in world-centered and bodycentered coordinates, and then subjected to three-dimensional kinematic analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 25 publications
0
9
1
Order By: Relevance
“…Contrary to previous work with healthy children (Ricken, Savelsbergh, & Bennett, 2004), who deal with the impact demands of an approaching object by lengthening deceleration time and movement time, we found that children with SHCP exhibited a reduced deceleration time in the moving ball condition compared to the stationary ball condition. At present it is not clear why we observed these differences in the timing of the reaching movement.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Contrary to previous work with healthy children (Ricken, Savelsbergh, & Bennett, 2004), who deal with the impact demands of an approaching object by lengthening deceleration time and movement time, we found that children with SHCP exhibited a reduced deceleration time in the moving ball condition compared to the stationary ball condition. At present it is not clear why we observed these differences in the timing of the reaching movement.…”
Section: Discussioncontrasting
confidence: 99%
“…A program was developed to identify key events in the displacement and velocity profiles of linear and angular data. Based on previous research on reaching in healthy children (Ricken, Savelsbergh, & Bennett, 2004) and children with cerebral palsy (Utley & Sugden, 1998;Volman et al, 2002) the following kinematic variables were extracted: peak velocity in the horizontal and vertical direction (PVX and PVY), movement time (MT), and deceleration time (i.e., time after peak wrist velocity until the moment of contact) in the horizontal and vertical direction (TAPVX and TAPVY). Trunk contribution was quantified by calculating the excursion of trunk lateral flexion, trunk flexion, and trunk rotation, where excursion is the sum of the angular change over time.…”
Section: Dependent Measures Of Reaching Performancementioning
confidence: 99%
“…Based on previous research on reaching in children without SHCP [11] and children with SHCP [1,2,13], the following linear kinematic data of the wrist movements were extracted: Initiation time of the reach, movement time (MT), wrist peak velocity (PVX and PVY), deceleration time of the wrist (TAPVX and TAPVY) and wrist velocity prior to contact (VPTC). Wrist peak velocity, wrist velocity prior to contact and deceleration time of the wrist were calculated relative to a world-centred and a body-centred frame of reference.…”
Section: Dependent Measuresmentioning
confidence: 99%
“…Deceleration time was represented by the time after peak velocity until the moment of contact. The walking velocity prior to contact (walk-VPTC) was calculated over the last 60 ms prior to contact [11], as well the average walking velocity, which was calculated by dividing the movement time by distance walked. Finally, we calculated the ratio between the peak velocity of walking and the maximum walking velocity measured prior to the experiment.…”
Section: Dependent Measuresmentioning
confidence: 99%
See 1 more Smart Citation